The Effects of Face Mask Usage on Ocular Structures in Children During the COVID-19 Pandemic - Bediz Özen; Hakan Öztürk (Galenos Yayinevi, 2022)
Aim:To determine the effects of face mask usage on ocular structures in children during the coronavirus disease-2019 (COVID-19) pandemic.Materials and Methods:Forty-two children's ocular data from the pandemic period were compared with the same children's ocular data from the pre-pandemic period.Results:Their mean age was 14.6±2.1 (9-18) years initially. The tear film break-up time values of the children with a mask in the pandemic period were significantly shorter than those of the children without a mask in the pre-pandemic period (9.35±1.40 vs. 12.10±1.05 seconds, p=0.033). There was no staining in any case in the pre-pandemic period, while minimal punctate epithelial corneal staining pattern was determined in 4 (9.5%) children in the pandemic period. The Schirmer test 1 value detected in the pandemic period was similar to the value detected in the pre-pandemic period (11.14±2.07 vs. 12.03±1.01 mm, p=0.127). Additionally, there were no significant changes in visual acuities, central corneal thicknesses, anterior chamber depths, lens thicknesses, and axial lengths between the pre-pandemic and pandemic periods (p>0.05).Conclusion:To the best of our knowledge, this is the first study to date to evaluate the effects of face mask usage on ocular structures in just children. The use of face masks may cause increased tear evaporation and dry eye in pediatric cases. Educating children about the correct use of face masks can be important. Thus, possible ocular surface changes which may occur relating to masks can be prevented, and children may be more willing to use masks. Increased mask compliance may also indirectly help protect children from the virus.